A (des)motivação do aluno pelo ensino de história ao final do nível fundamental em uma escola pública municipal de Goiânia - Macêdo, Júnio Matildes (2018)
The research on students' (dis) motivation for school teaching of History at the fundamental level was sparked by our concerns about experiences in the public networks of the State of Goiás and the municipalities of Goiânia and Aparecida de Goiânia, over a little more than a decade as professor of this discipline. Bzuneck (2001) states that it is the motivation that causes the person to move towards a certain action. Motivation happens when the person sees their interest contemplated in the process. Arroyo (2013) points out the denial of student interests in the school system, when the "authorships" (experiences, knowledge, interests, needs) of these students and even of teachers are denied (silenced, invisible) in this context, provoking demotivation by teaching offered. To understand this problem, this work of bibliographical and field research adopted the qualitative study of data. The data were collected using the participant observation method, the application of questionnaires and the recording of a focus group with open questions. It is also a case study and an action research. Sacristán (2000) states that, although there are institutional constraints, the teacher has a margin of autonomy in his pedagogical work with which he can try to break with external conditioning. This work is based on the hypothesis that the teacher's methodology, in its relation to the curriculum and the didactic resources instrumented in its teaching practice, are important elements to understand the object of this research - the student's (dis) motivation. Nevertheless, we recognize that student motivation is a complex problem that requires more research than other elements. This work points out and highlights the historical trajectory of our country, in which public and private sectors seek to control school education through measures that maintain the status quo of privileged social strata. In this context, Monteiro (2009) highlights the centrality of curricular texts and textbooks / textbooks in the conduct of the educational reforms of our Republic. The research observed and questioned (questionnaire and focus group) History teachers and students of the final stage of elementary education of a school unit of the municipal network of Goiânia of the western region. Subsequently, the research suggested and followed the application of a teaching-learning methodology mediated by the teacher and carried out by the students, in which they choose a theme and a way to develop it in the classroom. The objective is to stimulate the autonomy of students as central subjects of the teaching-learning process.